Effects of plyometric versus optimum power load training on components of physical fitness in young male soccer players - Ribeiro, J.; Teixeira, L.; Lemos, R.; Teixeira, A. S.; Moreira, V.; Silva, P.; Nakamura, F. Y. (International Journal of Sports Physiology and Performance, 2020)
Purpose: The current study aimed to compare the effects of plyometric (PT) versus optimum power load (OPL) training on physical performance of young high-level soccer players. Methods: Athletes were randomly divided into PT (horizontal and vertical drills) and OPL (squat+hip thrust exercises at the load of maximum power output) interventions, applied over 7 weeks during the in-season period. Squat and countermovement jumps, maximal sprint (10 and 30 m), and change of direction (COD; agility t test) were the pretraining and posttraining measured performance variables. Magnitude-based inference was used for within- and between-group comparisons. Results: OPL training induced moderate improvements in vertical squat jump (effect size [ES]: 0.97; 90% confidence interval [CI], 0.32-1.61) and countermovement jump (ES: 1.02; 90% CI, 0.46-1.57), 30-m sprint speed (ES: 1.02; 90% CI, 0.09-1.95), and COD performance (ES: 0.93; 90% CI, 0.50-1.36). After PT training method, vertical squat jump (ES: 1.08; 90% CI, 0.66-1.51) and countermovement jump (ES: 0.62; 90% CI, 0.18-1.06) were moderately increased, while small enhancements were noticed for 30-m sprint speed (ES: 0.21; 90% CI, -0.02 to 0.45) and COD performance (ES: 0.53; 90% CI, 0.24-0.81). The 10-m sprint speed possibly increased after PT intervention (small ES: 0.25; 90% CI, -0.05 to 0.54), but no substantial change (small ES: 0.36; 90% CI, -0.40 to 1.13) was noticed in OPL. For between-group analyses, the COD ability and 30-m sprint performances were possibly (small ES: 0.30; 90% CI, -0.20 to 0.81; Delta=+1.88%) and likely (moderate ES: 0.81; 90% CI, -0.16 to 1.78; Delta+2.38%) more improved in the OPL than in the PT intervention, respectively. Conclusions: The 2 different training programs improved physical performance outcomes during the in-season period. However, the combination of vertically and horizontally based training exercises (squat + hip thrust) at optimum power zone led to superior gains in COD and 30-m linear sprint performances.